Role of Endothelin-1 Receptor Antagonist in Reducing Perioperative Pulmonary Arterial Hypertension after Surgical Correction of Ventricular Septal Defect (Cardiovascular Journal, 2016)
Background: This study was designed to determine the role of oral ambrisentan, an endothelin-1 receptor, in reducing perioperative pulmonary arterial hypertension during surgical correction of ventricular septal defect.Methods: This study was carried out among 54 patients of ventricular septal defect with pulmonary arterial hypertension undergoing surgical correction. The patients were divided into two groups; study group received oral ambrisentan, an endothelin-1 receptor antagonist peri-operatively, starting one week before surgery. Pulmonary arterial pressure was measured by echocardiography, cardiac catheterization and directly from pulmonary artery during surgical procedure.Results: Pulmonary arterial pressure was reduced significantly in the group in which oral amrisentan was given perioperatively. There was further reduction of pulmonary arterial pressure at discharge from hospital and at one month follow-up.Conclusion: Oral ambrisentan can reduce pulmonary arterial pressure perioperatively in patients underwent surgical correction of ventricular septal defect.Cardiovasc. j. 2016; 9(1): 55-59